Роль волонтерського руху в сучасній Україні - Іванов, Є. В. (ХНУРЕ, 2023)
This work is devoted to the volunteer movement and its role in modem Ukraine. The work analyzes the historical development of volunteerism in Ukraine and its current state, examining various factors that have influenced the growth and impact of volunteer work in the country. Additionally, the study discusses the benefits of volunteerism for both individuals and society as a whole and highlights the challenges and obstacles that volunteers face in Ukraine. The research draws on a range of sources, including reports, articles, and official data. Overall, this work provides a comprehensive overview of the volunteer movement in Ukraine and its importance for social development in the country.